PENGARUH MODEL TGT (TEAMS GAMES TOURNAMENT) BERBASIS ICT TERHADAP HASIL BELAJAR SISWA KELAS V DI SD NEGERI 106865 BANDAR PAMAH - Saragih, Putri Yani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model based on ICT on the learning outcomes of fifth-grade students at SD Negeri 106865 Bandar Pamah in the subject of science, particularly on the topic of ecosystems and food chains. The research used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 17 students selected by total sampling. The instrument was a 15-item multiple-choice test, which had been validated for reliability and item difficulty. Data analysis showed that the average pretest score was 54.06 and the posttest score was 76.88. The average N-Gain score was 0.50, categorized as moderate. Normality tests showed the data were normally distributed, and the paired t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest scores. It can be concluded that the ICT-based TGT learning model positively affects students' learning outcomes. This model is recommended as an innovative learning strategy in elementary schools to improve learning achievement and student engagement.